Exploratory content analysis of direct-to-consumer pet genomics: What is being marketed and what are consumers saying? - Nikki E Bennett; Silvio Ernesto Mirabal Torres; Peter B Gray (PLoS ONE)
Mars Petcare introduced the first direct-to-consumer domestic dog genetic test in 2009 and Basepaws introduced the first direct-to-consumer cat genetic test in 2016. Social science research has evaluated numerous aspects of the human direct-to-consumer market, yet no such exploration has evaluated the occurrence of pet owners pursuing pet genetic tests. Using a mixed methods approach, we conducted an exploratory content analysis of direct-to-consumer pet genetic company webpages and consumer reviews shared on Amazon. Initial data reviews indicated some companies may be key industry players, relative to others. Our results present content frequency for each group (key industry players, all other companies), though the primary themes for each remained the same. Analysis showed genetic companies are primarily sharing product and purchasing information, along with trustworthiness to establish the merit of the company and their products. Companies also used statements directed towards pet owners that are suggestive of both pets and "pet parents" benefiting from the test results. The primary themes identified in consumer reviews involved consumers sharing their perception about the tests (e.g., accuracy), what aspects of the test results they focused on (e.g., breed information), and experiences with using the test (e.g., ease of use). Amazon reviews were primarily positive, though the companies with smaller review numbers had higher percentages of negative and ambiguous sentiments. Of interest, reviews most often indicated tests were being used to determine a pet's breed identity, while companies most frequently promoted the health advantages of using their products. Reviews revealed some consumers respond to tests by sharing their pet's results with someone or by altering their pet's care. Considering these results in addition to the growing popularity of this industry and the advancements of genomic technology, further research is needed to determine the role pet genetic testing may have in society and on human-animal relationships.